Inhibition or promotion: the impact of carbon emission trading on market structure: evidence from China - Zhang, Gong; Bi, Shulei (Frontiers in Energy Research, 2023)
Market structure serves as a crucial basis for government economic policies and the formulation of competitive strategies by businesses. It determines the formation of prices, the functioning of supply and demand relationships, the degree of competition, and exerts a significant influence on market economies. This paper first deduces the theoretical implications of carbon emissions trading on market structure and its regulating factors-based Theory of the Firm. It then utilizes the quasi-natural experiment of China’s pilot carbon emissions trading policy implemented in 2013, employing DID model, to empirically examine the policy effects and influencing mechanisms of carbon emissions trading on market structure. We find that carbon emissions trading policies can significantly inhibit market concentration and promote the development of market liberalization. This conclusion remains robust after a series of rigorous tests. Additionally, the analysis of dynamic effects reveals a noticeable lagged and incremental impact of carbon emissions trading policies on market structure. The negative adjustment of market concentration due to carbon emissions trading policies initiates in the policy’s starting year and gradually intensifies in the third phase. As expectations towards the policy stabilize, the negative adjustment decreases, and the short-term effects of carbon emissions trading policies are greater than the long-term effects. To verify the role of carbon emissions trading policies in influencing market structure during their implementation, a mechanism analysis based on cost and benefit perspectives is conducted. The results suggest that carbon emissions trading policies not only increase the environmental costs for industry-leading companies but also reduce the potential gains from market structure adjustments. Therefore, we propose promoting market competition, encouraging technological innovation, and strengthening transparency and regulation while considering differences in market structure. The findings of this paper provide new policy insights for promoting high-quality economic development and deepening market structure reforms in the context of the dual carbon goals.